An In-depth Exploration of an Unexamined Reliquary in the Church of Mar Tadros-Blat, Syria - Dana Khouli (Studies in Ancient Art and Civilization)
This article explores an unstudied, though not recent, discovery – a sarcophagus-shaped reliquary discovered in the village of Blat in Homs, Syria. The research aims to shed light on its cultural and historical importance. By conducting a detailed analysis of its carvings and symbolic iconography, the study seeks to unravel the religious motifs embedded in its design and interpretation, elucidating their connections with saints, pivotal figures intricately associated with sarcophagus reliquaries. Furthermore, the discussion investigates the incorporation of what is known as the circulation system, shedding light on regional religious practices and traditions. It also aims to determine whether the reliquary was openly displayed or kept hidden. The current condition of the reliquary emphasizes its continued reverence and preservation within the religious community.